A Policy Reform Framework for Mother Tongue-Based Multilingual Education in the Philippines - Aperocho, Maico Demi (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The current Mother Tongue-Based Multilingual Education [MTB-MLE] policy in the Philippines is beset with numerous issues, and this adversely affects the quality of basic education provided across regions. To address this, this policy paper suggests reviewing the current MTB-MLE policy through a more systematic policy reform mechanism that is participatory. This way, all concerned stakeholders in the Filipino education community contribute to the growth of the basic education instruction in the country by ensuring proper implementation of a mother tongue-based instruction policy. Anchored on the Rational Choice Theory (Becker, 1976), which believes on the following assumptions: individualism, optimality, structures, self-regarding interests, and rationality, this policy paper suggests a framework that the Department of Education can utilize in reviewing the existing policy and creating feasible decisions to improve the instruction in basic education. The proposal also drew inspiration from how the Bilingual Education Act of the United States of America became a promising legislation that has emphasized the importance of multicultural and multilingual classrooms in the country.